Malignant melanoma bone marrow infiltration induced coagulation dysfunction and spinal epidural haematoma with paraplegia: a case report and literature review - Liu, Songhua; Zhang, Baode; Shi, Yan; Guo, Jing; Yin, Weihua; Xu, Qinqin; Liu, Jinzhu; Min, Shaoxiong (Frontiers in Medicine, 2025)
Malignant melanoma bone marrow infiltration induced coagulation dysfunction and spinal epidural haematoma with paraplegia is extremely rare. It typically presents as anemia, coagulation dysfunction or disseminated intravascular coagulation, immune thrombocytopenia. In severe cases, it can lead to spinal epidural hematoma, compressing the spinal cord and nerve roots, resulting in motor and sensory dysfunction, and even paraplegia. Due to the rarity and complexity of this condition, it is prone to misdiagnosis or delayed diagnosis, ultimately leading to a poor prognosis. This paper reports the case of a 14-year-old female who was urgently admitted to the emergency department with low back pain for 1 month, accompanied by systemic mucous membranes bleeding and ecchymosis for half a month, numbness and incomplete paralysis in both lower limbs for 3 days. Laboratory tests indicated pancytopenia and abnormal coagulation function. Magnetic resonance imaging: T11-L1 epidural irregular abnormal signals in the spinal canal, with a range of about 16 mm × 17 mm × 65 mm. Further physical examination revealed that a large, cauliflower-like black mole on the right scalp, which had been present since childhood and had recurrently ulcerated without healing. Bone marrow aspiration biopsy confirmed the diagnosis of malignant melanoma with bone marrow infiltration, leading to coagulation dysfunction and SEH with paraplegia. However, despite 2 months of aggressive symptomatic and supportive treatment, the child ultimately succumbed to malignant melanoma forever. This report shares our experience with the diagnosis and treatment of this case, highlighting the necessity of thoroughly reassess the medical history and conduct a detailed physical examination.